Hubungan Iklim Madrasah Dengan Kinerja Tenaga Kependidikan Di Madrasah Ibtidaiyah Se-Kabupaten Purwakarta - Nasir, Tatang Muh; Irawan, Irawan; Yulistiawati, Lilis; Pasyola, Naufal Ridho; Warman, Oman (Fakultas Agama Islam Universitas Ibn Khaldun Bogor, 2023)
Performance improvement can be affected by compensation. This of course can be a burden for madrasas/institutions, if performance improvements must always be related to compensation. This study intends to find out: the climate of madrasas in Purwakarta Regency, the performance of teaching staff in Purwakarta Regency, and the relationship between Madrasah Climate and the Performance of Education Personnel in Purwakarta Regency. This study uses a quantitative approach model. The study population was all madrasas in Purwakarta Regency, totaling 389 madrasahs, with a sample of 43 respondents from 43 schools. The sample was taken using a random sampling technique. As for data collection obtained by distributing questionnaires / questionnaires. This study obtained the results: Madrasah climate in Purwakarta Regency has a score of 94, is in the 76% - 99% category, namely the very good category, the performance of the Education Staff is in a high qualification, with a mean (average) value of 4.58, namely in the interval 3.6 – 4.5, and 3). Madrasah climate with the performance of teaching staff has a significance value of 0.001. The significance value is 0.001 <0.05, so both have a correlation or relationship. The results of the calculation of the correlation coefficient obtained are 0.480, with a position interval of 0.40 - 0.599 which means that it has a degree of relationship with a moderate correlation. The result of the calculation of the coefficient of determination (R square) is 0.230, meaning that the contribution of the madrasah climate variable (X) to the performance of educational staff (Y) is 23% and the rest is influenced by other aspects such as: leadership style, positive support from family, as well as career development.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//